The role of the scouting movement in contributing to some of the sustainable development goals of race in Iraq - Assist. Prof. Husam Malik Saleh (Global Scientific Publishing, 2025)
In general, the research was aimed at identifying the role of the Scout movement in contributing to the achievement of some of the development goals in Iraq. The problem of the research was the difficulties and obstacles facing the Scout movement in achieving these. goals. The researcher assumed that the Scout movement has a role to contribute to the achievement of some of the Sustainable Development Goals recognized by the United Nations 2015. The researcher used several approaches to address this research problem: the analytical descriptive approach to describe and analyze the roles played by the Scout movement and the survey, inductive aGoal 3, Goal 4, Goal 13, Goal 16, and the researcher concluded that there is harmony and great similarity to the goals of the Scout movement and the Sustainable Development Goals. This makes their work a complementary unit to the other. This shows that the most appropriate organizations can achieve the Sustainable Development Goals are the Scout movement organizations. The researcher recommends that government institutions support the efforts of Scout movements and organizations because of their major active role in building a better society by contributing to the achievement of sustainable goals.
Keywords: Sustainable Development Goals 3, 4, 13, 16 Scout organizations, Scout challenges and difficulties, media, awareness raising, Scout education